Identifikasi Padi Sawah Di Desa Tombolango Kecamatan Sangkub Kabupaten Bolaang Mongondow - Djakaria, Eric; Ngangi, Charles Reijaaldo; Lumingkewas, Jelly Ribka Danaly (AGRI-SOSIOEKONOMI, 2023)
This study aims to identify lowland rice farmers in the village of Tombolango, District of Sangkub, North Bolaang Mongondow Regency. The data analysis used in this study was the purposive sampling method, from the total population of lowland rice farmers in the tombolango village, which has an area of lowland rice farming under 1 ha and above 1 ha. Based on these criteria, 15 samples were taken as respondents. The data collection method in this study was carried out by collecting primary data and secondary data. Primary data is raw data taken by researchers in the field from the source and obtained from direct interviews, while secondary data is data obtained from the government or local agencies. The results of this study indicate that the identification of lowland rice farmers in the village of tombolango, Sangkub District, shows the characteristics of lowland rice farmers, namely the type of seeds used, the amount of production, the selling price, fertilizers, herbicides, insecticides, the number of initial workers, tractor machines and threshing machines, and farmer incomes ranging from IDR 20,000,000.